Teknososiopreneur: Karakteristik dan Minat Mahasiswa - Ati Harianti; Budi Suryowati; Hermawan Seftiono (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The purpose of this study was to find out the characteristics of students' technosociopreneurship in the form of Integrity, Togetherness, Independence, Excellence, and Innovation which refer to the values in the vision of Trilogy University and students' interest in becoming a technosociopreneur. Of the 2,289 students spread across 12 study programs, 439 students were used as samples using simple random sampling technique. Descriptive statistical methods and the t-test for the difference between the two averages are used in analyzing data regarding techno-sociopreneur characteristics and techno-sociopreneur interests. The results of the study show that students have Techno-Socio-Sociopreneur characteristics with an average score of 4.08 out of a maximum scale of five or it is said that students have Techno-Socio-Sociopreneur characteristics. There are differences in the characteristics of techno-sociopreneurs between students who are working and not working and there is no difference in interest in becoming a techno-sociopreneur between students who are working and not working, between men and women, and between FEB and non-FEB students.Keywords: Integrity; Independence; Superiority; Innovation; Techsociopreneur  AbstrakTujuan penelitian ini untuk mengetahui bagaimana karakteristik keteknososiopreneuran mahasiswa berupa  Integritas, Kebersamaan, Kemandirian, Keunggulan, dan Inovasi yang mengacu pada nilai-nilai pada visi Universitas Trilogi dan minat mahasiswa untuk menjadi seorang teknososiopreneur. Dari sebanyak 2.289 mahasiswa yang tersebar di 12 program studi, sebanyak 439 mahasiswa dijadikan sebagai sampel dengan teknik pengambilan simple random sampling. Metode Statistik deskriptif  dan Uji t untuk beda dua rata-rata digunakan dalam melakukan analisis terhadap data mengenai karakteristik keteknososiopreneuran dan minat berteknososiopreneur. Hasil penelitian menunjukan bahwa mahasiswa memiliki Karakteristik Keteknososiopreneuran dengan nilai rata-rata 4,08 dari  maksimal skala lima atau dikatakan mahasiswa memiliki karakteristik keteknososiopreneuran. Ada perbedaan karakteristik keteknososiopreneuran antara mahasiswa yang sudah bekerja dan belum bekerja dan tidak ada perbedaan minat untuk menjadi seorang teknososiopreneur antara mahasiswa yang sudah bekerja dan belum bekerja, antara pria dan wanita, dan antara mahasiswa FEB dan NonFEB.Keywords: Integritas; Kemandirian; Keunggulan; Inovasi; Teknososiopreneur